Rancang Bangun dan Evaluasi Sistem Informasi Pembayaran Elektronik pada Universitas Jambi - Marlina, Leni; Marzal, Jefri; Mauladi, Mauladi (Prodi Sistem Informasi FST Universitas Jambi, 2018)
This study aims to create an electronic payment information system (e-payment) to facilitate the process of data payment management at Jambi University. This research uses design and creation research strategy. The research used software development method which adapted from Rational Unified Process (RUP) model. RUP is a model with a very flexible process framework that can be customized for various situations in system development. In addition, this study also aims to evaluate information systems developed to determine the level of system usability. Based on the results of research, it is found that with the e-payment system applied to the University of Jambi greatly facilitate and accelerate the processing of payment data. After seeing the user's view of the usefulness of the developed system, the e-payment system is good in adjective rating, grade scale, and system acceptability range. The results of the system usability test show that the e-payment system is in very good category and acceptable by the user.